An IoT based Automated and Intelligent System for Patient Health - Nivedita, S.; Kala, R. (Journal of Soft Computing Paradigm, 2022)
The Internet of Things (IoT) has remained extensively to connect accessible medical resources and provide smooth, dependable, and in effect of healthcare services to patients, and it has the potential to disrupt healthcare innovation. Health monitoring system using IoT application is the recent trend in medical field, by discovering the potential of the technology. Humans are incrassating the several issues and precocious death due to numerous illness, and by deficiency in providing medical treatment to the patients. To obtain the solution to this issue, a real time health monitoring system is proposed based on the recent technology such as IoT. Enhanced and intelligent healthcare system is the representation of developed and prosperous nation. The proposed method improves the monitoring system by shrinking the use of sensors, which have been attempted to exploit the new technology to obtain the solution for the healthcare problem currently society is facing, and a remote healthcare system is designed. The proposed automated and intelligent system involved with the different phases such as revealing the vitality of patient’s using sensors, sends patients data to cloud storage and thus providing it to the doctors to utilize it, which will help to access and observe the patient’s well-being improvement away from hospital locations. The proposed automated and intelligent system is used to interconnect the accessible medical resources and offer smart, reliable, and effective healthcare system to the people. An IoT architecture with customized healthcare applications have been developed to support remote health monitoring system.
Keywords: Internet of Things; ThingSpeak; Arduino Board; Sensor